ANALISIS STRATEGI PENINGKATAN MUTU PENDIDIKAN MELALUI PROGRAM TAHFIDZ METODE TAJDIED DI MI MUHAMMADIYAH 21 KAPAS BOJONEGORO - Muhammad Yusron; Muhammad Tamyiz (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
This research was conducted due to the background of improving the quality of madrasah education that must be accompanied by the quality of its religion which remains superior. The school must be able to answer these challenges with a quality tahfidz program for graduates. In learning requires the development of content and context. The problem formulation of this thesis is First, how to use the tahfidz program strategy with the tajdied method, Second, how to improve the quality of education, Third, what are the supporting and inhibiting factors in improving the quality of education through the tahfidz program with the tajdied method at MI Muhammadiyah 21 Kapas Bojonegoro. This research was conducted with a descriptive qualitative approach. Data collection techniques using interviews, participant observation and documentation. Data analysis consists of data reduction, data presentation and drawing conclusions. Checking the validity of the data is done through extension of participation, persistence of observation, triangulation, and peer examination. The results of the study concluded that (1) improving the quality of education through planning, selection, modification of the local curriculum, the learning process up to evaluation, (2) learning strategies that are often used are classical reading and listening, (3) the learning techniques used are singing and storytelling techniques for the introduction of keywords and clapping techniques to distinguish long and short mad readings (4) evaluations are carried out continuously at the end of each lesson, the results are written in the students’ achievement book and in the teacher's daily journal.Keywords: education, quality improvement, tajdied method. Penelitian ini dilakukan kerena dilatar belakangi peningkatan mutu pendidikan madrasah harus dibarengi dengan mutu agamanya tetap unggul. Pihak sekolah harus bisa menjawab tantangan tersebut dengan program tahfidz yang bermutu bagi lulusan. Dalam pembelajarannya membutuhkan pengembangan konten maupun konteksnya. Rumusan masalah dari tesis ini adalah Pertama, bagaimana penggunaan strategi program tahfidz metode tajdied, Kedua, bagaimana peningkatan mutu pendidikan, Ketiga, apa faktor pendukung dan penghambat dalam peningkatan mutu pendidikan melalui program tahfidz metode tajdied di MI Muhammadiyah 21 Kapas Bojonegoro. Penelitian ini dilaksanakan dengan pendekatan kualitatif deskriptif. Teknik pengumpulan data menggunakan wawancara, observasi partisipan dan dokumentasi. Analisis data terdiri dari reduksi data, penyajian data dan penarikan kesimpulan. Pengecekan keabsahan data dilakukan melalui perpanjangan keikutsertaan, ketekunan pengamatan, triangulasi dan pemeriksaan teman sejawat. Hasil dari penelitian menyimpulkan bahwa (1) peningkatan mutu pendidikan melalui perencanaan, seleksi, modifikasi kurikulum lokal, proses pembelajaran hingga evaluasi, (2) strategi pembelajaran yang sering digunakan adalah baca simak klasikal, (3) teknik pembelajaran yang digunakan adalah teknik bernyanyi dan cerita untuk pengenalan kata kunci dan teknik tepuk untuk membedakan panjang dan pendek bacaan mad (4) evaluasi dilaksanakan terus menerus setiap akhir pembelajaran, hasilnya ditulis pada buku prestasi peserta didik dan pada jurnal harian guru.Kata Kunci: pendidikan, peningkatan mutu, metode tajdied